The Effect Of Islamic Banking Financial Ratio On The Financial Performance - Yuwana Wangsa Putri Iskandar; Andi Sulfati; Asbi Amin (IECON, 2024)
This study explores the impact of Net Operating Margin (NOM), Operating Expenses to Operating Income (BOPO), Non-Performing Financing (NPF), and Capital Adequacy Ratio (CAR) on the financial performance of Islamic banks listed under the Financial Services Authority (OJK) from 2018 to 2023. Using secondary data obtained from financial reports available on the banks' official websites, the study employed a purposive sampling method. The population consisted of Islamic banks registered with OJK during the study period, narrowing down to 6 banks with 36 observations as the final sample. Data analysis utilized multiple linear regression to examine the relationships between the variables, accompanied by hypothesis testing to determine their statistical significance. The findings indicate that NOM and BOPO did not show a significant influence on the financial performance of the sampled Islamic banks. However, NPF and CAR demonstrated a substantial and statistically significant impact. These results underscore the importance of managing credit risk and maintaining adequate capital reserves to ensure financial stability and performance in Islamic banking. This study provides valuable insights for policymakers and bank managers to focus on strengthening risk management practices and capital adequacy to sustain and enhance the financial health of Islamic banking institutions in Indonesia.